Trinity, Economy, and Scripture : Recovering Didymus the Blind - Hicks, Jonathan (Jonathan Douglas), 1984- (Book collections on Project MUSE., 2015)
"The 4th-century teacher, Didymus the Blind, enjoyed a fruitful life as head of an episcopally-sanctioned school in Alexandria. Author of numerous dogmatic treatises and exegetical works, Didymus was considered a stalwart defender of the Nicene faith in his heyday. He duly attracted the likes of Jerome and Rufinus to his school. Contemporary scholarship has focused most of its attention on understanding him as an exegete, especially focusing on his exegetical vocabulary and the driving assumptions behind his particular method of reading Scripture. The theological literature has been somewhat neglected. In this study, Jonathan Hicks makes the claim that Didymus's exegesis can only be understood in all its fullness in light of his theological commitments. His acute differences with Theodore of Mopsuestia on the proper reading of the prophet Zechariah cannot be understood as merely methodological. Animating Didymus's reading of the prophet is a lively understanding of Trinitarian missions. Recognizing the comings of the Son and the Spirit to Israel is essential in locating the prophet's message properly within the one divine economy of revelation and salvation that culminates in the Incarnation of Christ. Hicks argues that Didymus is instructive here for today's Church both on the level of praxis (we should adopt some of his reading practices) and on the level of theoria (his Trinitarian account of Scripture's origin and ends is fundamental to a fully Christian understanding of what Scripture is)."